Exploring thermodynamically downhill nanostructured peptide libraries: from structural to morphological insight. Issue 2 (3rd December 2014) - Rasale, Dnyaneshwar B.; Biswas, Sagar; Konda, Maruthi; Das, Apurba K.
Abstract : Biocatalytic evolution of thermodynamically downhill nanostructured peptide libraries in hydrogel states are envisaged. Abstract : Here, we report the biocatalytic evolution of Nmoc (naphthalene-2-methoxycarbonyl)-capped dynamic combinatorial peptide libraries in the hydrogel state. Our approach is to use a biocatalyst, which can bring up the peptide self-assembly via synthesis and in situ self-organization of peptide oligomers under physiological conditions. The enzyme drives the amplification of Nmoc-capped peptide oligomers and leads to the generation of dynamic combinatorial libraries under physiological conditions via a reverse hydrolysis reaction. The enzyme permits reversible peptide synthesis as well as peptide hydrolysis reactions, which generate a preferred nanostructured component through peptide self-assembly. Nmoc-F/FF and Nmoc-L/LL systems have been used successfully to generate Nmoc-F3 and Nmoc-L5 as preferred components in the dynamic peptide libraries, which form helical nanostructures. The control experiment with a Nmoc-L/LLL system depicts the selection and preferred formation of a Nmoc-L5 library member via self-assembly. The library components are analysed by reverse phase high performance liquid chromatography (RP-HPLC) and mass spectrometry. The self-assembled nanomaterials are studied by rheology, fluorescence and time correlated single photon counting (TCSPC) spectroscopy. The secondary structure of the peptide components are analysed by FT-IR and circular dichroism (CD) spectroscopy. The self-assembled nanostructures are imaged by atomic force microscopy (AFM) and transmission electron microscopy (TEM).